Development of Interactive Learning Media Mobile Learning In Science for Class VIII Junior High School - Jodi Hardika; Ridwan Ridwan; Alwen Bentri; Ramalis Hakim; Rayendra Rayendra; Fetri Yeni J (Jurnal Penelitian Pendidikan IPA, 2024)
This research focuses on the development of interactive mobile learning media for science subjects in eighth-grade junior high school. The identified problems are the lack of student engagement and the limitations of easily damaged learning media. Additionally, educators face difficulties in using technology in the teaching and learning process. This study uses the research and development (R&D) method with a 4-D model. The product's validity was assessed by six experts—two media experts, two language experts, and two subject matter experts—who rated it as "Highly Valid" with an average percentage of 92%, 89%, and 97%, respectively. The practicality test showed that the media is very practical, with an average percentage of 87% from teachers and 96.7% from students. The effectiveness of the media was measured by the gain score, which showed a value of 0.62, categorized as "Moderate," and the average student learning outcome after using the media was 81.4, categorized as "Very Good." Based on these results, the interactive mobile learning media for science subjects in eighth-grade junior high school has been proven to be valid, practical, and effective in improving student learning outcomes